2009
DOI: 10.1038/jes.2008.74
|View full text |Cite
|
Sign up to set email alerts
|

A simple pharmacokinetic model to characterize exposure of Americans to Di-2-ethylhexyl phthalate

Abstract: A simple pharmacokinetic model to predict concentrations of metabolites of di-2-ethylhexyl phthalate, DEHP, in humans starting from intakes of DEHP was developed and applied. This model predicts serum and urine concentrations of five DEHP metabolites: MEHP, 5oxo-MEHP, 5OH-MEHP, 5cx-MEPP, and 2cx-MMHP. The model was calibrated using data from an individual who dosed himself with 48.5 mg DEHP, and then took blood and urine samples over a 44-h period. The calibrated model was then used in two applications: one on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 35 publications
0
40
1
1
Order By: Relevance
“…On a body weight basis, this 48.5 mg translates to 650 mg/kg. This differs from median intakes determined from urine measurements and the creatinine correction approach that ranges from about 1 mg/kg/day in the United States (Lorber et al, 2010) to 5 mg/kg/day based on urine measurements from German study participants (Wittassek et al, 2007b). As observed, this dose is clearly elevated above background and this is observed also in the urine concentration data.…”
Section: Self-dosed Individualcontrasting
confidence: 66%
“…On a body weight basis, this 48.5 mg translates to 650 mg/kg. This differs from median intakes determined from urine measurements and the creatinine correction approach that ranges from about 1 mg/kg/day in the United States (Lorber et al, 2010) to 5 mg/kg/day based on urine measurements from German study participants (Wittassek et al, 2007b). As observed, this dose is clearly elevated above background and this is observed also in the urine concentration data.…”
Section: Self-dosed Individualcontrasting
confidence: 66%
“…Individual variations in (oxidative) metabolism have been discussed as a third possibility for a weaker correlation between MEHP and oxidized metabolites than within the oxidized metabolites [129,147]. However, Lorber et al [147] have shown in their PBPK-model of DEHP that, due to the elimination kinetics of the different DEHP metabolites, depending on the time point of exposure, and the time point of sample collection (morning or afternoon sample), the ratio between MEHP and the oxidized metabolite 5OH-MEHP can vary between 2.89 and 5.4, whereas the ratio between the oxidized metabolites 5OH-MEHP and 5oxo-MEHP varies within a close margin of 1.50-1.78. Therefore, most of the weaker correlation of MEHP with the oxidized metabolites can be explained by differences in elimination kinetics between these metabolites and not inter-individual differences in phthalate metabolism.…”
Section: Human Metabolism -Biomarkers Of Exposurementioning
confidence: 99%
“…Despite its simplicity, a most recent re-evaluation with a more sophisticated model once again accentuated its merits for exposure estimation (Lorber et al, 2009).…”
Section: Discussionmentioning
confidence: 99%